Identifying risk factors for carbapenem-resistant Acinetobacter baumannii carriage upon admission: a case-case control study - Debby Ben-David; Bar Roshansky; Yael Cohen; Niv Sylvie; Lili Raviv; Ariel Zimerman; Orna Schwartz (Antimicrobial Resistance and Infection Control)
Abstract Background Active screening programs and early detection of asymptomatic carriers are effective in preventing carbapenem-resistant Acinetobacter baumannii (CRAB) dissemination in healthcare facilities. This study aims to identify risk factors associated with CRAB carriage among patients upon admission to an acute care hospital. Methods A case-case-control study was conducted at an acute care hospital. Starting in June 2020, new admissions to medical wards underwent rectal and buccal screening. Patients with CRAB or carbapenem-susceptible A. baumannii (CSAB) carriage were compared to controls, randomly selected from patients with negative cultures, at a one-to-one ratio. Multinomial logistic regression using a backward stepwise method was employed to identify factors associated with CRAB and CSAB carriage. A Chi-square Automatic Interaction Detector analysis was also conducted to further elucidate risk factors. Results The study included 115 CRAB carriers, 117 CSAB carriers and 121 controls. Increasing age was associated with a reduced risk of CSAB (OR: 0.96, p < 0.001) and CRAB carriage (OR: 0.97, p = 0.02), while higher Charlson Comorbidity Index scores increased the risk for both. CRAB carriage was significantly associated with admission from long-term acute care hospitals (OR: 7.68, p < 0.001) and presence of pressure ulcers (OR: 89.98, p < 0.001). Decision tree analysis identified pressure ulcers, prior location, and Charlson score as key predictors, with CRAB carriage reaching 77.3% in patients admitted from long-term acute care hospitals with pressure ulcers. Conclusion Pressure ulcers were strongly associated with the carriage of both susceptible and resistant strains of A. baumannii. CRAB carriage was predominantly observed in patients transferred from long-term acute care hospitals, highlighting the need for targeted screening in this high-risk population.